2022
DOI: 10.1021/acs.jpclett.2c00996
|View full text |Cite
|
Sign up to set email alerts
|

Harvesting the Triplet Excitons of Quasi-Two-Dimensional Perovskite toward Highly Efficient White Light-Emitting Diodes

Abstract: Utilization of triplet excitons, which generally emit poorly, is always fundamental to realize highly efficient organic light-emitting diodes (LEDs). While triplet harvest and energy transfer via electron exchange between triplet donor and acceptor are fully understood in doped organic phosphorescence and delayed fluorescence systems, the utilization and energy transfer of triplet excitons in quasitwo-dimensional (quasi-2D) perovskite are still ambiguous. Here, we use an orangephosphorescence-emitting ultrathi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…In addition to the isolation or luminescence functions shown in Figure 3a,b, organic molecules with both isolation and luminescence properties can also be introduced into POC-WLED. Recently, Yu et al [75] reported a POC-WLED architecture with an ultrathin organic layer as the orange component and perovskite as the blue component, as shown in Figure 3c. It is found that the inserted spacer can block holes and inhibit the concentration quenching in the organic light-emitting layer.…”
Section: Perovskite-organic Stacking Balanced Coupling Emissionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the isolation or luminescence functions shown in Figure 3a,b, organic molecules with both isolation and luminescence properties can also be introduced into POC-WLED. Recently, Yu et al [75] reported a POC-WLED architecture with an ultrathin organic layer as the orange component and perovskite as the blue component, as shown in Figure 3c. It is found that the inserted spacer can block holes and inhibit the concentration quenching in the organic light-emitting layer.…”
Section: Perovskite-organic Stacking Balanced Coupling Emissionmentioning
confidence: 99%
“…Recently, Yu et al. [ 75 ] reported a POC‐WLED architecture with an ultrathin organic layer as the orange component and perovskite as the blue component, as shown in Figure 3c. It is found that the inserted spacer can block holes and inhibit the concentration quenching in the organic light‐emitting layer.…”
Section: Perovskite‐organic Stacking Balanced Coupling Emissionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14] The existence and the impact of singlet and triplet states in low-dimensional materials and in different perovskite materials has been investigated by several groups providing different approaches how to overcome the splitting and hence improve the emission. [14][15][16][17][18] For low-dimensional semiconductors, enhancing the photoluminescence is not only possible via transitions between singlet-triplet states but also via phonon-assisted radiative recombination. [19][20][21][22] Furthermore, efficient transfer processes are crucial for bright luminescence.…”
Section: Introductionmentioning
confidence: 99%
“…[ 14 ] The existence and the impact of singlet and triplet states in low‐dimensional materials and in different perovskite materials has been investigated by several groups providing different approaches how to overcome the splitting and hence improve the emission. [ 14‐18 ]…”
Section: Introductionmentioning
confidence: 99%